Etiological Spectrum of Acute Confusional States in Young Adults Presenting to Emergency Departments - Zahid Ullah Khan, Hashmat Ullah, Hammad Khan, Mashal Khan, Khalid Zaheen, Nigar Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute confusional state (ACS), clinically aligned with delirium, is characterized by acute onset of impaired attention, altered awareness, and fluctuating cognition. Although widely studied in elderly populations, limited evidence exists regarding its etiological distribution in young adults. This study aimed to determine the etiological spectrum and associated outcomes of ACS among young adults presenting to a tertiary care emergency department. Methods: The study was an observational, hospital-based study that was carried out in the Department of Emergency Medicine, Lady Reading Hospital, Peshawar, between May 2022 and April 2023. Youths aged 18-40 years with clinically diagnosed ACS were recruited. Patients with chronic neurocognitive disorders and those with primary psychiatric conditions but not of organic nature were excluded. Standardized clinical assessment and pertinent lab and radiological tests were conducted to identify underlying etiologies. The SPSS version 26.0 was used to analyze the data. Results :150 patients were used in the analysis (mean age 28.4 ± 6.1 years; 58.7% men). The most common causes were metabolic causes (34.0) and infectious (26.7), toxicological (18.0), neurological (12.7), and systemic/other causes (8.6). Most metabolic etiologies were hypoglycemia (12.0%) and hyponatremia (10.7), with meningitis and encephalitis being the most common infectious. The overall mortality was 6.7, with the highest mortality occurring on the infectious and neurological cases. The prolonged hospital stay was considerably linked to infectious and neurological etiologies (p = 0.02). Conclusion: Metabolic and infectious causes predominate among young adults with ACS, with infectious and neurological etiologies associated with worse outcomes. Keywords: Acute confusional state, delirium, young adults, emergency department, etiology